Effect of Two Species of Cyanobacteria as Biofertilizers on Characteristics and Yield of Chickpea Plant - Burjus, Sanaa; Jawad, Abdul latif; Al-Ani, Nabeel (Iraqi Journal of Science, 2023)
The cyanobacteria strains were used in bioreactors to produce biomass. The total biomass after one month in suitable conditions such as efficient gas exchange, powerful light source and suitable medium composition was 7.99 mg/ml for N. commune and 5.83mg/ml for A. circinalis. These algae were applied alone or mixed in two rates (5 or 10 ml/ 100 g compost); Azotobacter chroococcum was used before 7 days of harvesting or with other cyanobacteria species. The total Nitrogen showed 1.84% with Azotobacter, however the nitrogen in mix culture was 1.80% mean while, the control treatment was 1.49%.. These results indicate that we can reduce chemical fertilizers by 1/4 or may 1/2 dose of normal requirement on growth and yield of chickpea plant.